Click-Based Journalism: The Impact of Analytics and Algorithms on Online Media Editing - Nedeljković, Marko (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2023)
This paper points out the growing impact of web analytics and algorithms on the process of selection made by journalists and editors, evaluation and creation of news and media content, as well as their distribution to the audience. More specifically, the paper analyzes the impact of data on the behavior of the audience and its interests on news value assessment and online media editing. In a large number of media, the changes brought about under the influence of "digital metrics" lead to an increasingly intense shift from the traditional gatekeeping practice, which implies "an editorial way of news value assessment", to a gatewatching practice, which implies "click-based news value assessment". Therefore, terms such as "measurable journalism", "algorithmic journalism" and "automated journalism" are increasingly used even in theory to indicate the growing influence of analytics and algorithms on modern online media and everyday journalistic practice. The scale of this influence is best evidenced by the fact that the new criteria for assessing the news value are already supplementing traditional professional standards and even becoming the primary news selection criteria for a growing number of newsrooms. Therefore, the aim of this paper is to point out in more detail the theoretical considerations on this issue, the changes that are taking place in journalistic practice under the influence of analytical services and increasingly advanced algorithms, but also the consequences for online media editing because the impact of new technologies on news production is increasing and will pose a major challenge for journalism in the future.
Keywords: online journalism, online media editing, digital metrics, web analytics, gatekeeping, gatewatching, algorithms, news selection, news distribution, digital audience